PENGARUH INFORMASI DUNIA KERJA DAN PENGALAMAN PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN MENTAL MENGHADAPI DUNIA KERJA SISWA KELAS XII PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN SMK NEGERI 2 SUKOHARJO TAHUN AJARAN 2013/2014 - Septyanita, Cyndi (Jurnal Nosel, 2014)
The purpose of this research as followws to know the positive influence between employment work information and  work industry practice experience toward mental readiness into work world of the student class XII in light vehicle mechanic program SMK Negeri 2 Sukoharjo either partially or simultaneously. The study was conducted using quantitative research by inferensial statistical analysis planning. The population consists of 181 students. The sample consists of 125 students. The technique for collecting data is using questionnaire. Based on the research result we can coclude: there are positive and significant relationship between employment work information with mental readiness into work world of the student class XII in light vehicle mechanic program SMK Negeri 2 Sukoharjo with taccount>ttable = 9.459 >2.616. There are positive and significant relationship between work industry practice experience with mental readiness into work world of the student class XII in light vehicle mechanic program SMK Negeri 2 Sukoharjo with and taccount>ttable = 8.650 >2.616.There are positive and significant relationship between employment work information and work industry practice experience with mental readiness into work world of the student class XII in light vehicle mechanic program SMK Negeri 2 Sukoharjo with Faccount>Ftable = 59.123>4.783.